2020
DOI: 10.1017/s0007114520005140
|View full text |Cite
|
Sign up to set email alerts
|

Associations of carbohydrates and carbohydrate-rich foods with incidence of type 2 diabetes

Abstract: Dietary carbohydrates have long been expected to be associated with risk of type 2 diabetes; however, the associations for many carbohydrates and carbohydrate-rich foods remain inconclusive. This study analysed associations between intakes of six types of carbohydrates and thirteen carbohydrate-rich foods with incident type 2 diabetes in 26 622 participants (61 % women) in the Malmö Diet and Cancer Study in southern Sweden. Dietary intake was assessed at baseline (1991–1996) by using a modified diet history me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Several studies suggest that high consumption of SSBs may be positively associated with the risks of obesity and related complications ( 12 , 59–75 ), such as nonalcoholic fatty liver disease (NAFLD) ( 60 , 64 ), T2DM ( 61–63 , 65 , 72 , 76–80 ), stroke ( 71 ), coronary heart disease (CHD) ( 71 , 81 , 82 ), high blood pressure ( 15 , 70 , 73 ), and CVD mortality ( 83–85 ). However, in the prospective cohort study by Olsson et al ( 86 ), high intake of SSBs was not associated with an increased risk of T2DM. Other studies reported that high SSB consumption was associated with MetSyn in men but not women, which may be explained by differential hormone levels between males and females ( 81 , 82 , 87 ).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Several studies suggest that high consumption of SSBs may be positively associated with the risks of obesity and related complications ( 12 , 59–75 ), such as nonalcoholic fatty liver disease (NAFLD) ( 60 , 64 ), T2DM ( 61–63 , 65 , 72 , 76–80 ), stroke ( 71 ), coronary heart disease (CHD) ( 71 , 81 , 82 ), high blood pressure ( 15 , 70 , 73 ), and CVD mortality ( 83–85 ). However, in the prospective cohort study by Olsson et al ( 86 ), high intake of SSBs was not associated with an increased risk of T2DM. Other studies reported that high SSB consumption was associated with MetSyn in men but not women, which may be explained by differential hormone levels between males and females ( 81 , 82 , 87 ).…”
Section: Resultsmentioning
confidence: 84%
“…Several prospective cohort studies have shown that high sucrose or fructose consumption was not associated with the T2DM incidence or risks ( 86 , 91–96 ), nor was it even associated with a reduced risk of T2DM ( 78 , 91 , 97 , 98 ) ( Table 3 ). In contrast, Warfa et al ( 80 ) showed in a prospective cohort study that high sucrose consumption was associated with an increased risk of T2DM, and the study by Montonen et al ( 77 ) showed high fructose intake, but not sucrose intake, was associated with an increased T2DM incidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An inverse association between linoleic acid (which belongs to n-6 series of PUFA) intake and T2DM was reported by NHS, NHSII, and HPFS researches, particularly when linoleic acid replaced isocalorically SFA or carbohydrates [31]. Regarding carbohydrates, a study carried out in Sweden found inverse associations between intake of monosaccharides and fruits with T2DM, and positive associations for disaccharides and sweets [32]. Other studies have focused on glycemic index and glycemic load as the causal factors responsible for T2DM incidence [33,34], although it has also been suggested that glycemic index and glycemic load might be less useful tools to evaluate quality of carbohydrates than dietary fibre and whole-grain content [35].…”
Section: Discussionmentioning
confidence: 94%
“…During the literature research, the risk of type 2 diabetes is significantly increased with the long‐term consumption of high glycemic index (GI) foods (Eyinla et al., 2021). At the same time, the delay of glucose absorption and the reduction of blood sugar requirement would be obtained with low GI foods, which could enhance blood sugar control (Olsson et al., 2021). Thus, it is an effective and significant method for developing low GI functional food components to lighten or even cut the occurrence of diabetes (Eyinla et al., 2021).…”
Section: Introductionmentioning
confidence: 99%